Knowledge, attitude and practice on recycling activity among primary school students in Hulu Langat, Selangor - Sobri, Nur Aisyah; Abdul Rahman, Haliza (Kalpana Corporation, 2016)
The objective of the paper was to study the knowledge, attitude and practice of recycling activities among 2 primary school students in Hulu Langat, Selangor, Malaysia. A comparative cross-sectional study was carried out among primary school student in Kajang and Semenyih, Hulu Langat, Selangor. A number of 188 primary school students were selected as respondents. A set of questionnaire was used to obtain the information about socio-demographic, knowledge, attitude and practices of recycling activity. For knowledge level, the urban schools have 75.7% in good knowledge while rural schools have 71.3%. For the attitude level, 72.3% of urban school have good attitude while only 53.2% of rural school have good attitude. Both school shown practices in satisfactory level which is 74.5% in urban while 62.8% in rural school. For the mean difference, there was a mean difference between knowledge (p<0.05, p= 0.003), attitude (p<0.05, p= 0.008) and practices (p<0.05, p= 0.047) between rural and urban school. Furthermore, there was an association between attitude (p<0.05, p=0.025) and practices (p<0.05, p=0.034) towards the rural and urban school. However, there was no association between knowledge and location of school (p>0.05, p= 0.249). There was an association between knowledge (p<0.005, p=0.002) and attitude level (p<0.005, p=0.001) to the practices level. For conclude the primary school from both rural and urban school students have a good knowledge and attitude toward recycling but moderate in recycling practices. Thus, the students should be nurtured to increase their practices in recycling activities, such as having environmental education at home and in school, joining recycling awareness campaign and recycle activities.